(untitled) (East West Medical College Journal, 2025)
Stroke is one of the most significant contributors to disability and death worldwide, with an especially high burden in low- and middle-income countries like Bangladesh. Contributing factors to the growing prevalence of stroke in Bangladesh include hypertension, diabetes, smoking, and limited access to timely healthcare. While the FAST (Face, Arms, Speech, Time) approach helps in the clinical recognition of stroke, delays in treatment persist, often leading to higher mortality and disability rates. This review explores the stroke burden in Bangladesh, identifying critical challenges in diagnosis and care. Additionally, it offers imaging recommendations based on international guidelines, adapted to local healthcare realities. The review also emphasizes the importance of timely interventions and key performance indicators (KPIs) for improving stroke outcomes. EWMCJ Vol. 13, No. 2, July 2025: 69-75